2005
DOI: 10.1093/geront/45.6.764
|View full text |Cite
|
Sign up to set email alerts
|

Variation by Disability in State Predictors of Medicaid 1915c Waiver Use and Expenditures

Abstract: Increased community-based-care capacity appears to be an important factor in efforts to expand the availability of Medicaid community-based care. Federal policies that address state resource issues may also spur growth in community-based long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This economic measure was positively associated with rates of use and expenditures for individuals with developmental disabilities but not related to use and expenditures for older and working-age individuals (N. A. Miller, Kitchener, et al, 2005). Although it is a proxy for state economic resources, it may also be a proxy for the availability of informal care.…”
Section: Discussionmentioning
confidence: 97%
“…This economic measure was positively associated with rates of use and expenditures for individuals with developmental disabilities but not related to use and expenditures for older and working-age individuals (N. A. Miller, Kitchener, et al, 2005). Although it is a proxy for state economic resources, it may also be a proxy for the availability of informal care.…”
Section: Discussionmentioning
confidence: 97%
“…The year 2003 was selected as a midpoint between the report years of 2000-07. State characteristics such as these are often useful in understanding state decision-or policy-making (Baron and Straus, 1989;Miller et al, 2005;Soule and Real, 2001;Zimmerman, 1988). The data for team-level characteristics were taken from Webster et al (2003), the only source for team characteristics.…”
Section: State and Team Characteristicsmentioning
confidence: 99%
“…Statistically non-significant effect for the CON on CE is supported by other studies (Miller et al [2005]; Grabowski et al [2003]), which have found that states that repealed the CON program, saw little to no change in their cost structure. This coupled with the fact that the estimated cost function showed that increase in stitutional care resulted in declining cost upto a certain point, and increasing after that, which suggests that nursing homes and ICFMR may already be operating at less than full capacity.…”
Section: Discussionmentioning
confidence: 56%